2023
DOI: 10.3390/medicina59020251
|View full text |Cite
|
Sign up to set email alerts
|

The Prone Lateral Approach for Lumbar Fusion—A Review of the Literature and Case Series

Abstract: Lateral lumbar interbody fusion is an evolving procedure in spine surgery allowing for the placement of large interbody devices to achieve indirect decompression of segmental stenosis, deformity correction and high fusion rates through a minimally invasive approach. Traditionally, this technique has been performed in the lateral decubitus position. Many surgeons have adopted simultaneous posterior instrumentation in the lateral position to avoid patient repositioning; however, this technique presents several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…There has been a rapid increase in the popularity of minimally invasive techniques, XLIF being one of them [15]. More than 20% of spinal fusions being performed in the United States utilize the XLIF or DLIF approach [16,17], while 14% of spinal fusions being performed in the United Kingdom utilize the XLIF or DLIF approach [18]. While there is a higher utilization of the transforaminal lumbar interbody fusion (40.4%), posterior lumbar interbody fusion (28.1%), and anterior lumbar interbody fusion (15.8%) approaches in the United Kingdom [18], the XLIF and DLIF procedures are the newest approaches and are gaining utility.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a rapid increase in the popularity of minimally invasive techniques, XLIF being one of them [15]. More than 20% of spinal fusions being performed in the United States utilize the XLIF or DLIF approach [16,17], while 14% of spinal fusions being performed in the United Kingdom utilize the XLIF or DLIF approach [18]. While there is a higher utilization of the transforaminal lumbar interbody fusion (40.4%), posterior lumbar interbody fusion (28.1%), and anterior lumbar interbody fusion (15.8%) approaches in the United Kingdom [18], the XLIF and DLIF procedures are the newest approaches and are gaining utility.…”
Section: Discussionmentioning
confidence: 99%
“…Farber et al ( 31 ) demonstrated in a case series that the single-position PL transpsoas approach resulted in successful treatment for adult patients (n=29), with well-tolerated and acceptable clinical and radiographic outcomes. Barkay et al ( 32 ) assessed their experience with the traditional PL interbody fusion technique that was previously described by Pimenta et al ( 15 ). The most common complication experienced by patients (45%) was hip flexor pain on the ipsilateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SPS has been demonstrated to reduce manpower necessary to perform the flip and importantly improves patient safety [ 137 , 147 ]. Regarding intraoperative blood loss, radiation exposure, complications, and reoperation rates, SPS offers similar or even better outcomes as that of dual-position surgery [ 145 , 148 , 149 ].…”
Section: Recent Advancesmentioning
confidence: 99%
“…This positioning offers a more familiar and spacious area for the surgeon to operate, facilitating easier pedicle screw placement and posterior decompression, as deemed necessary [ 151 , 152 , 153 ]. Furthermore, studies have demonstrated that adopting a prone position enables enhanced correction of sagittal plane imbalance attributed to an augmented lumbar lordosis [ 148 , 154 ], resulting in better segmental lordosis correction when compared to L-SPS ( Table 4 ) [ 155 ]. As the procedure evolved, accompanying advancements were made in the instruments designed to sustain a stable prone position amidst the new lateral forces [ 153 ].…”
Section: Recent Advancesmentioning
confidence: 99%
See 1 more Smart Citation